(untitled) (Third Sector Social Economic Review, 2025)
International capital movements and the activities of multinational corporations are affected by various socioeconomic and political factors. Among these factors, low labor costs are one of the important factors that attract foreign investments. Foreign direct investment inflows are often attributed to unskilled labor, including child labor. Especially in developing countries, child labor continues to exist as an important social problem that attracts increasing research attention and mobilizes joint efforts of international organizations. This study aims to empirically examine the interaction between foreign direct investment inflows and child labor in developing countries using panel causality analysis. The analysis was conducted with the data for the period 2000-2023 for 37 selected countries with high child labor among underdeveloped countries. In the empirical analysis of the study, cross-sectional dependence was first investigated, and the stationarity levels of the variable series were determined using the Pesaran CIPS unit root test. Subsequently, a Dumitrescu-Hurlin causality analysis was conducted to examine the causal relationship between the dependent variable child labor and the independent variables foreign direct investment, gross domestic product per capita, trade openness, and population. The findings indicated a unidirectional causal relationship from foreign direct investment inflow to child labor. No causal relationship was found from other macroeconomic variables to child labor.